Effect of COVID-19 Patients Flow Rate from ER to LPD on COVID-19 Patients Healing Rates at RSUP DR. Sardjito’s ER - Muchammad Choerul Arifin; Naelufa Syifna Wifaqotul Muna; Arizka Yuliana; Lingga Sanjaya Putra Mahardhika; Albert Hosea Santoso; Dwi Ertiningsih (Journal of the Indonesian Mathematical Society, 2022)
COVID-19 or Coronavirus Disease-19 which first appeared in December 2019 has spread around the world, one of which is Indonesia. The spread of the COVID-19 has affected all areas of human life and the most affected area is health. It can be known from the number of COVID-19 patients in numerous national referral hospitals, one of which is RSUP Dr. Sardjito. This large number of COVID-19 patients often causes a high number of bed occupancy rates and has an impact on special rooms, the room for COVID-19 patients who come to the hospital for the first time or the Emergency Room (ER) and the room for COVID-19 patients from the ER who was declared seriously ill or inpatient. Furthermore, imbalance between the number of ER and Long-stay Patient Department (LPD) and the number of COVID-19 patients result in a decrease in the flow rate of COVID-19 patients from the ER to the long stay patient department. To find out the impact of that flow rate, this research was conducted using Richard's Curve and Kaplan-Meier Estimator. The results of this research show effect of flow rate which can be observed from the probability of COVID-19 patients who recovered or died in each special room. The probability of a COVID-19 patient in the ER recovered is greater than the probability of a patient died. Meanwhile, the probability of a COVID-19 patient in the long stay patient department recovered is smaller than the probability of a patient died.